The Representation of the Iraqi Protests in the New York Times: A CDA Analysis - Saeed Mahdi Abdulraheem (RIRAI Publisher, 2023)
The spark of the October revolution in Iraq ignited on the first day of October and persisted for forty days, interrupted only by religious occasions. It regained momentum on October 25, 2019, continuing as a significant sociopolitical event. From its inception, the revolution faced suppression by the Iraqi government, with the use of tear gas, live weapons, and hunting weapons against protesters. The Iraqi revolution captured global media attention, becoming a focal point of coverage worldwide. This research paper employs Critical Discourse Analysis (CDA) using Teun van Dijk's Socio-Cognitive Model to investigate how The New York Times represents the Iraqi protests in its headlines. Data is collected from The New York Times' official website, with a focus on headlines related to the Iraqi demonstrations from October 2019 to the present time. The analysis comprises two levels: Micro Level Analysis scrutinizes linguistic features, while Macro Level Analysis explores broader sociocultural and cognitive contexts. The research aims to answer questions regarding the portrayal of the protests, linguistic strategies employed, framing of actors, and reflections of social and cognitive contexts. The study acknowledges limitations, including the exclusive use of headlines and the scope limited to The New York Times. However, the research contributes valuable insights into media discourse, biases, power dynamics, and the influence of language on shaping public understanding of complex sociopolitical events. The findings have implications for media studies and communication research, prompting critical engagement with media representations and the potential impact on public perceptions and discourses.